Globális problémák és a környezet - Székely, Mózes (Szociológiai Szemle, 2024)
The article presents the findings of a survey conducted in 2000 by interviewing 1000 persons, a representative sample of Hungary's adult population. The results show that at the dawn of the new millennium people think about poverty and environment as one of the most dangerous questions worldwide. From global point of view wars, famine and diseases belong here as well, whereas in Hungary the problem of "Alcohol, smoking and drug-using" is evidently considered to be the most important. The results challenge the popular view about the possibilities of individuals' contribution. Two third of the participants mention concrete actions, with which the individuals are willing to contribute to the solution of these problems. In the public mind, there is a multifaceted but homogeneous system of concepts outlined around the expression of 'global problems'. Firstly, the arrangement of the general terms of serious phenomena varies by different aspects: e.g. certain things are important at world scale, and others for Hungary specifically. Secondly, the complex events both close to and far from us are categorized and classified similarly, and moreover, the ranking of importance are alike at nearly all socio-demographical groups.